2022
DOI: 10.1002/prp2.949
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of epigenetic reader proteins by apabetalone counters inflammation in activated innate immune cells from Fabry disease patients receiving enzyme replacement therapy

Abstract: Fabry disease (FD) is a rare X‐linked disorder of lipid metabolism, characterized by the accumulation of globotriaosylceramide (Gb3) due to defective the lysosomal enzyme, α‐galactosidase. Gb3 deposits activate immune‐mediated systemic inflammation, ultimately leading to life‐threatening consequences in multiple organs such as the heart and kidneys. Enzyme replacement therapy (ERT), the standard of care, is less effective with advanced tissue injury and inflammation in patients with FD. Here, we showed that MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…63 In a pilot study, peripheral blood mononuclear cells and neutrophils were separated from eight FD patients receiving continuous ERT64 blood samples. 63 Importantly, apabetalone treatment of these cells downregulated the gene expression of proinflammatory cytokine secretion, such as IL-6, IL-1β, IL-12, and CCL-2, induced by lipopolysaccharide (LPS) or IFNγ. 63 Also, apabetalone significantly reduced the production of reactive oxygen species, possibly by suppressing the transcription of NADPH oxidase 2 (NOX2).…”
Section: ■ Apabetalone In Neurological Disordersmentioning
confidence: 99%
See 3 more Smart Citations
“…63 In a pilot study, peripheral blood mononuclear cells and neutrophils were separated from eight FD patients receiving continuous ERT64 blood samples. 63 Importantly, apabetalone treatment of these cells downregulated the gene expression of proinflammatory cytokine secretion, such as IL-6, IL-1β, IL-12, and CCL-2, induced by lipopolysaccharide (LPS) or IFNγ. 63 Also, apabetalone significantly reduced the production of reactive oxygen species, possibly by suppressing the transcription of NADPH oxidase 2 (NOX2).…”
Section: ■ Apabetalone In Neurological Disordersmentioning
confidence: 99%
“…63 Importantly, apabetalone treatment of these cells downregulated the gene expression of proinflammatory cytokine secretion, such as IL-6, IL-1β, IL-12, and CCL-2, induced by lipopolysaccharide (LPS) or IFNγ. 63 Also, apabetalone significantly reduced the production of reactive oxygen species, possibly by suppressing the transcription of NADPH oxidase 2 (NOX2). 63 Furthermore, the study also confirmed the involvement of BET in the beneficial effects of apabetalone in inflammation and oxidative stress associated with FD.…”
Section: ■ Apabetalone In Neurological Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms underlying liver transplant rejection have received considerable attention lately [5,6], with these studies mainly focusing on cellular and humoral immunity, as well as innate immunity responses as related to liver transplant rejection [7][8][9]. Dendritic cells, monocytes, macrophages, and neutrophils have also all been shown to play a vital role in regulating innate immunity [10,11]. The occurrence of immune rejection is closely related to chemokines, proinflammatory cytokines, and signaling pathways [12,13].…”
Section: Introductionmentioning
confidence: 99%